Pediatric dysphagia: Is interarytenoid mucosal height significant?. (23rd January 2019) - Padia, Reema; Coppess, Steven; Horn, David L.; Parikh, Sanjay R.; Hoang, Jennifer; Faherty, Amy; DeMarre, Kimberley; Johnson, Kaalan
Abstract : Objectives: The clinical significance of the interarytenoid mucosal height (IAMH) in pediatric dysphagia, ranging from normal anatomy to a laryngeal cleft, is unknown. This study seeks to evaluate a cohort of patients who underwent evaluation of their IAMH during microdirect laryngoscopy (MDL) for associations between IAMH and dysphagia as diagnosed on preoperative videofluoroscopic swallow study (VFSS). Methods: A retrospective case series of 1, 351 patients who underwent MDL between 2011 and 2016 were reviewed for intraoperative evaluation of IAMH using our interarytenoid assessment protocol. After exclusions, 182 patients were divided into three groups: 1) thickened diet: VFSS with recommendation for thickened liquids (n = 82 of 182; 45.1%), 2) normal diet: VFSS with allowance of thin liquids (n = 19 of 182; 10.4%), and 3) control: no VFSS performed (n = 81 of 182; 44.5%). Results: There was no difference in IAMH between groups ( P = 0.35). Power analysis was able to achieve > 80% power to detect an effect size of ≥ 0.5 (1–5 mucosal height scale). The majority of patients in each group had an IAMH above the false vocal folds (thickened diet: 57.3%, normal diet: 57.9%, control: 64.2%). There were similar percentages of patients in each group with an IAMH at or below the true vocal folds (thickened diet: 4.9%, normal diet: 5.3%, control: 6.1%). Conclusion: There was no significant association between IAMH and preoperative thickened liquid recommendation in this cohort. This data fails to support the hypothesis that the IAMH is an independent etiological factor for pediatric pharyngeal dysphagia. Further studies comparing IAMH with outcomes after feeding therapy and surgery may better clarify this relationship between anatomy and physiology. Level of Evidence: 4. Laryngoscope, 129:2588–2593, 2019